Live Weight and Sex Effects on Sensory Quality of Rubia de El Molar Autochthonous Ovine Breed Meat - Eugenio Miguel; Belén Blázquez; Felipe Ruiz de Huidobro (Animals, 2021)
Fifty-six Rubia de El Molar ovine breed lamb carcasses were divided into 8 groups (n = 7 per group) according to weight (10, 15, 20 and 25 kg) and sex (male and female) to study the effect of these factors on meat sensory characteristics, assessed by means of a trained panel. Heavier animals showed a more-springy meat and also received lower scores for pleasantness. Assessors gave lower scores for flavour and pleasantness in female meat. A high correlation was detected between hardness and springiness, number of chews, and pleasantness. Juiciness, greasiness, and flavour were also sensory variates highly correlated. Pleasantness was only correlated to hardness. Changes from 10 to 25 kg did not affect juiciness, greasiness, flavour, and number of chews. There are no significant differences in the sensory quality of lambs slaughtered at 10 and 15 kg live weight, and also between 20 and 25 kg groups. Heavy carcasses (20 and 25 kg) showed a more hard and springy meat than light carcasses (10 and 15 kg). Besides, the 10 and 15 kg animals group received higher scores for pleasantness. This work showed differences in suckling lambs’ meat sensory parameters between Rubia de El Molar and other ovine breeds.